Quality of Services at RSUD X, Emotions and Satisfaction of Covid-19 Patients - Shine Pintor Siolemba Patiro; Hendrian Hendrian; Prisila Damayanty; Ramdhan Kurniawan; Surya Adi Sasmita (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2023)
This research aims toto reveal the influence of service quality consisting of tangible, reliability, responsiveness, empathy, and assurance on the positive emotions of RSUD patientsX Solo Cityand its influence on satisfaction. The problem formulation in this research is related to the gap that will be discussed in this research. The gaps that will be discussed in this research relate to theoretical gaps, empirical gaps, and method gaps. The theoretical gap in this research is related to the basic theory that will be used in this research, namely service quality theory, emotion theory, and customer satisfaction theory. This research involved 300 respondents who were former Covid-19 patients who had been treated at referral hospitals in the cities of Semarang and Solo. Data collection uses a questionnaire with a survey method. The data analysis technique uses Structural Equation Modeling (SEM) with the help of the SMART PLS 3 application. The results of this study show that all dimensions of RSUD service quality have a positive and significant effect on patient emotions, and patient emotions have a positive effect on satisfaction. The limitations of this research are related to the scope of respondents and areas used as well as the variables contained in this research model.